What she knew - Macmillan, Gilly (New York : William Morrow, an imprint of HarperCollinsPublishers, 2015)
Rachel Jenner's son Ben vanishes in a park one day. Police are called, search parties go out, and Rachel, already insecure after her recent divorce, feels herself coming undone. As hours and then days pass without a sign of Ben, everyone who knew him is called into question, from Rachel's newly married ex-husband to her mother-of-the- year sister. Inevitably, media attention focuses on Rachel too, and the public's attitude toward her begins to shift from sympathy to suspicion.
Includes reader's guide.
Includes bibliographical references (pages 471-472).
Keywords: Missing children -- Fiction; Mothers and sons -- Fiction; Psychological fiction; Suspense fiction